2017
DOI: 10.1080/15320383.2017.1397098
|View full text |Cite
|
Sign up to set email alerts
|

Counter-Current Attrition Process (CCAP) to Remove Metals, Pentachlorophenol (PCP), Dioxins and Furans (PCDDF) from the 1-4-mm Fraction of Contaminated Soil

Abstract: The objective of this study was to evaluate the potential of a counter-current attrition process (CCAP) over 15 cycles for removing metals, pentachlorophenol (PCP) and polychlorinated dibenzo-p-dioxins and-furans (PCDDF) from contaminated soil. The CCAP, applied to the 1-4mm fraction of a contaminated soil, included five attrition steps (pulp density (PD) = 40% (w w-1), surfactant [BW] = 2% (w w-1), t = 20 min, T = 20°C) followed by one rinsing step. The water emerging from the first attrition step was treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The results showed that the contaminant removal yields obtained during 15 loops of the CCAP varied between 32 and 52% for As, 17 and 37% for Cr, 15 and 37% for Cu and 41% and 50% for PCDD/F. The removal yields of attrition observed in the present study were similar than those obtained by Guemiza et al (2017b) for the removal of metal(loid)s but higher for PCDD/F. The higher removal yields of organic contaminants in the current study can be explained by the higher initial concentration of PCDD/F in the S3 soil.…”
Section: Performance Of Attrition and Leaching Of Sludge Attrition Fo...supporting
confidence: 78%
See 2 more Smart Citations
“…The results showed that the contaminant removal yields obtained during 15 loops of the CCAP varied between 32 and 52% for As, 17 and 37% for Cr, 15 and 37% for Cu and 41% and 50% for PCDD/F. The removal yields of attrition observed in the present study were similar than those obtained by Guemiza et al (2017b) for the removal of metal(loid)s but higher for PCDD/F. The higher removal yields of organic contaminants in the current study can be explained by the higher initial concentration of PCDD/F in the S3 soil.…”
Section: Performance Of Attrition and Leaching Of Sludge Attrition Fo...supporting
confidence: 78%
“…The first series of the five attrition steps (L1) was conducted using fresh water. As mentioned by Guemiza et al (2017b), wastewater from the first stage of attrition is treated by flocculation-decantation in order to remove some of the contaminants (e.g. suspended matter).…”
Section: Decontamination Process At Pilot-scalementioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the levels of chlorinated phenolic compounds generated by PCP were below detection threshold. Guemiza et al (2017) investigated the use of counter-current attrition process (CCAP) to remove contaminants from soil including PCP. The CCAP treatment achieved a removal rate of 49% for PCP and was considered a suitable solution for industrial applications.…”
Section: Pentachlorophenolmentioning
confidence: 99%